Effect of biaxial stretching on thermomechanical properties of polylactide based nanocomposites. (2nd September 2016) - Ouchiar, S.; Stoclet, G.; Cabaret, C.; Addad, A.; Gloaguen, V.
Abstract: This work focuses, for the first time, on the structural evolution of Polylactide (PLA) and PLA-Talc nanocomposites upon biaxial stretching. Biaxial stretching is a widely used technique to improve the end-use properties of polymer films. Encountered in a large number of elaboration processes it involves important structural changes into the material which directly govern the properties gain. In this work the influence of both stretching conditions and clay content were addressed. Besides it is observed that while relatively low clay content, i.e. below 10 wt%, has a limited impact on the mechanical behavior, higher contents dramatically modify the latter and particularly decreases the stretchability of the material. It was also evidenced that both the stretching conditions and clay content influence the strain-induced structure. Particularly the presence of talc favors the formation of a crystalline structure upon stretching due to its nucleating ability. The mechanical behavior of the biaxially stretched samples has also been investigated. As a key point it was observed that while the as elaborated materials are brittle when uniaxially stretched at room temperature, the biaxially stretched ones exhibit a ductile behavior with achieved strains at break up to 100%. The origin of this brittle to ductile transition, assessed by means of in situ SAXS experiments, was found in the inhibition of the crazing mechanism for samples biaxially oriented under appropriate conditions. Graphical abstract: Highlights: Influence of talc content on the mechanical behavior of PLA upon biaxial stretching. Nucleating effect of talc on the strain-induced crystallization. Strain-induced structural evolution upon biaxial stretching. Brittle to ductile transition induced by texturation Macromolecular orientation involves crazing inhibition.